Screening of Endophytic Bacteria from Purwoceng Roots (Pimpinella pruatjan Molk.) Antibacterial Activity Against Staphylococcus aureus - Sartika GP (Journal of Biological Science and Education, 2021)
Most antimicrobial agents, antifungus or antibacterial have been isolated from plants. Purwoceng (Pimpinella pruatjan Molk.) is one of the potential plants that produced an antibacterial agent. But, the status of purwoceng as an endemic plaint in Central Java is